The government and the Indian - Moore, Leona Estel (My University, 1907)
Introduction: The history of the Indians in the United States from the time of the first occupation of the country by the whites has been one of forced migrations, always westward, to make way for the repeated encroachments of civilization. Before the arrival of the English they occupied both sides of the Alleghany Mountains from the Gulf of Mexico to Canada and New Brunswick. There were also some tribes, about whose early history little is known, occupying territory west of the Mississippi river. The eastern tribes may be divided into three great families, the Iroquois, the Algonquin, and the Mobilian, each speaking a language of its own, although different dialects were used by the tribes of each of the three families. Besides these, there were a few stragglers from the great western race of the Dahcotas and also several distinct tribes of the south. The first of these great families, the Iroquois, consisted of the Hurons, who dwelt between Lake Huron and Lakes Erie and Ontario, and the five tribes or nations who were in the territory that comprises the present state of New York. These were the Mohawks, the Oneidas, the Onodagas, the Cayugas, and the Senecas, to whom a sixth, the Tuscaroras, was afterward added. The Algonquins occupied practically all the territory, with the exception of that occupied by the Iroquois, from Hudson's Bay to the Carolinas and from the Atlantic to the Mississippi and Lake Winnipeg. The Delawares were along the Delaware river and its tributary streams, within the present limits of New Jersey and Pennsylvania. The Shawnees were a wandering tribe, who, during the latter part of the eighteenth century, settled in…
Citation: Moore, Leona Estel. The government and the Indian. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Native Americans; Early American History; Early American Settlers; Westward Expansion; Theses